Effectiveness of fungicides and Trichorderma spp. for the control of Lasiodiplodia spp. in ‘Persian’ lemon orchards in Veracruz - Camacho-Tapia, Moises; Leyva-Mir, Santos Gerardo; Bautista-Cruz, Marco Antonio; Vargas, Gustavo Almaguer; León, Maria Teresa Colinas; Pedraza, Juan Manuel Tovar (Revista Mexicana de Ciencias Agrícolas, 2021)
The descending death of ‘Persian’ lemon (Citrus latifolia Tan.) caused by Lasiodiplodia spp., is a high-importance disease. The intensity of lemon pruning increases the susceptibility and annual loss of up to 35% of trees, resulting in 60% reduction in production. During 2016 and 2017, in the municipality of Papantla, Veracruz it was assessed the effectiveness of chemical and biological control against Lasiodiplodia spp., after pruning. A complete block design was performed at random; five treatments were applied: methyl thiophanate (1 g L-1), thiabendazole (2.5 g L-1), chlorothalonil (3 g L-1), mancozeb (4 g L-1), Trichoderma harzianum + Trichoderma viridae (20 ml L-1) and a witness (without application). Two sprays were made aimed at trunk, branches and foliage up to drip point. The incidence and severity of the disease was evaluated every seven days after the first application. With the data, epidemiological models were adjusted and descriptive parameters such as: initial intensity, rate of increase and area under the disease progress curve were calculated. Methyl thiophanate fungicide was most effective in disease control, followed by thiabendazole.
Keywords: Lasiodiplodia spp.; descending death; disease control